2007
DOI: 10.1039/b617414k
|View full text |Cite
|
Sign up to set email alerts
|

266 nm photolysis of CF3I and C2F5I studied by diode laser gain FM spectroscopy

Abstract: Frequency modulated diode laser based absorption at 1.315 microm has been used to measure the Doppler lineshapes of the I((2)P(1/2)-(2)P(3/2)) transition in atomic iodine produced from the 266 nm photolysis of both CF(3)I and C(2)F(5)I. Wavelength resolved laser gain is seen following photolysis as excited iodine atoms ((2)P(1/2)) are produced with a quantum yield close to unity from photolysis of both parent molecules. Time resolved measurements were made and the nascent speed distribution and translational a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 41 publications
(55 reference statements)
1
26
0
Order By: Relevance
“…The detected signals were amplified using either one, or two, 500 MHz amplifiers (Minicircuits ZFL-500LN) as required, and then demodulated with reference to the rf signal applied to the EOM in an rf demodulator circuit (Pulsar Microwave). The resulting The nascent pure FM absorption profiles were extracted by the method used in our previous work [45]. …”
Section: Methodsmentioning
confidence: 99%
“…The detected signals were amplified using either one, or two, 500 MHz amplifiers (Minicircuits ZFL-500LN) as required, and then demodulated with reference to the rf signal applied to the EOM in an rf demodulator circuit (Pulsar Microwave). The resulting The nascent pure FM absorption profiles were extracted by the method used in our previous work [45]. …”
Section: Methodsmentioning
confidence: 99%
“…11,17 A glass tube containing molecular iodine (Aldrich, 499% purity), heated to approximately 10 1C above room temperature in order to increase the vapour pressure, was connected to a 1.5 m glass photolysis cell via Teflon tubing. 11,17 A glass tube containing molecular iodine (Aldrich, 499% purity), heated to approximately 10 1C above room temperature in order to increase the vapour pressure, was connected to a 1.5 m glass photolysis cell via Teflon tubing.…”
Section: Experimental and Analysismentioning
confidence: 99%
“…11,17 First, a numerical integration over a series of time intervals with limits separated by 100 ns of the recorded I and Q signals was performed. 11,17 First, a numerical integration over a series of time intervals with limits separated by 100 ns of the recorded I and Q signals was performed.…”
Section: Experimental and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A prime example in this category is the CF 3 I molecule, which has 18 more valence electrons than un-substituted methyl iodide. It has been the subject of numerous experiments in which I* quantum yields have been obtained [5][6][7][8][9][10][11][12][13][14][15][16][17][18] and its absorption spectrum has also been measured. [19][20][21][22] Theoretical studies of CF 3 I are much rarer, but ab initio calculations have also been reported for this system, 23,24 as well as a treatment of its photodissociation dynamics.…”
Section: Introductionmentioning
confidence: 99%